Exemplification in news narratives: stigmatizing and securitizing effects - Sellnow-Richmond, Deborah D.; Lukacovic, Marta N.; Sellnow-Richmond, Scott A. (Frontiers in Communication, 2024)
Exemplification, the use of emotionally evocative messages to elicit a response based on impression formation, are frequently present in news messages. The current study examined the use of positive versus negative exemplars in news stories to determine the role of stigmatization and securitization in these messages and whether this impacts perceptions of the importance and quality of news. Our research can serve to responsible journalists as an evidence-based resource to begin in critical and ethical assessment of the advantages and disadvantages of exemplars in reporting, especially during crises when issues of stigma or security threats are particularly relevant.